Rating agencies: an information privilege whose time has passed - Nicolas Véron (Bruegel, 2009)
Nicolas Véron argues rating agencies have failed the marketplace in the run-up to the crisis, as their risk assessment processes have been found wanting on a number of counts. It is not clear that conflicts of interests have been the root cause of this serious failure, even if such conflicts may have existed. More regulation of rating agencies will not be a sufficient response to the challenge posed by the agencies recent failings, and carries risks of its own. What is needed is a deeper change in the structure of the market for financial risk assessment services.
Keywords: 330; Ratingagentur; Kritik; Finanzmarktkrise; Bankenkrise